Test Bias in Employment Selection Testing A Visual Introduction - Stetz, Thomas A. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides students with a concise introduction to test bias from a psychometric point-of-view without statistics. It uses easy to understand graphs to explain complex technical approaches to test bias giving readers a highly sought-after knowledge enabling them to be better consumers of tests. Studies performed by the Society for Human Resource Management (SHRM) consistently show that selection is a key competency for Human Resource (HR) professionals. Knowledge of test bias is a key component to effectively and legally performing this highly valued HR function. Unfortunately, test bias is rarely covered in HR classes or is presented in a highly technical manner geared to individuals with strong statistical and mathematical backgrounds. This book, requiring no previous statistical or mathematical knowledge, can be used as a supplemental textbook for any class that deals with selection, staffing, or measurement at the undergraduate or graduate level.
Chapter 1: Introduction to Tests and Test Bias -- Chapter 2: Linear Regression -- Chapter 3: Differential Test Prediction -- Chapter 4: Measurement Variance -- Chapter 5: Differential Item Functioning -- Chapter 6: The 4/5ths Rule -- Chapter 7: Case Studies -- Glossary.
Keywords: Personnel management; Psychology, Industrial; Psychological tests; Human Resource Management; Organizational Psychology; Psychological Testing